National Inheritance Law: Looking at the Weaknesses and Challenges of Its Implementation in Indonesia - A.Sukmawati Assaad; Baso Hasyim; Yusmita Yusmita (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This article describes the inheritance law in Indonesia, namely customary inheritance law, Islamic inheritance law and Western civil inheritance law (BW). The three inheritance law systems have their respective adherents from the original community, descendants of both Muslim and non-Muslim. Thus, there is a pluralism of inheritance law in Indonesia; this is not the case regarding marriage which already has a legal umbrella, namely Law Number 1 of 1974 which is the result of the achievements of Indonesian Islamic jurists during the New Order era which was able to unite the Indonesian people in the form of legal unification. The unification and codification of inheritance laws that apply nationally would require a long process to achieve the goals and ideals of the Indonesian nation. The purpose of writing this article is to find out: 1. what is the form of the National Inheritance Law in Indonesia? 2. What are the results of the SWOT analysis of the National Inheritance Law in Indonesia? This study uses descriptive research methods, i.e. by exploring or photographing social situations that were studied thoroughly, broadly, and deeply. This article concludes that the national inheritance law in Indonesia is constitutionally enforceable. In addition, there is a need for the role of religion in contributing to the development of the inheritance law. However, it takes a great effort by the parties involved to socialize the law because there are still many inheritance disputes that occur in the community because they leave the legal institutions, both religious courts and general courts